Кам’яна індустрія стоянки Кобулеті - Манько, В.О.; Чхатарашвілі, Г.Л. (Археологія і давня історія України, 2020)
У статті розглянуто матеріали з кременю та
обсидіану з багатошарової ранньоголоценової стоянки Кобулеті. Розкопки стоянки були поновлені у
2019 р. Дослідження призвели до відкриття ділянки зі складною стратиграфією, на якій вдалося дослідити три однокультурних шари доби раннього голоцену. Основними характеристиками отриманих комплексів було використання відтискної техніки для отримання пластинчастих заготовок. Отримані пластинчаті заготовки використовувалися для виготовлення вкладнів мисливського
озброєння. Культура Кобулеті, що існувала протягом раннього голоцену, стала основою для формування низки неолітичних культур Закавказзя та Східної Європи. The Kobuleti site is located on the territory of the
Kobuleti village in Adjara (Georgia). The site was discovered
on the cape of the left bank of the Kintrishi
River. The cape formed by two ravines occupied the
area ca. 50 × 50 m, towering 16—25 m above the river
level. The site height above the sea level is 60 m. The
cape is composed of basalt rocks, only its upper part is
associated with sediments of a pack of paleosoils.
Geographically the site is connected with the Colchis
Plain which occupies the part of coastal territory.
The Kintrishi River flows along the southern part of
the plain at the very border with the foothills. Currently
the Colchis Plain is associated with a subtropical climate
zone but this does not mean that the climate was
the same at the beginning of the Holocene when the
site was abandoned. At the beginning of the Holocene
the territory of Western Georgia had a rather temperate
climate where coniferous species of trees including
fir, spruce, and pine were widespread.
The inhabitants of the site, therefore, chose a strategically
important place for settlement, only 20 km from
the sea coast, on the banks of the river flowing into the
Black Sea, on the border of two landscape zones of the
plain and foothills.
In total, 1529 artifacts have been found, including
911 made of flint and 618 made of obsidian.
The technique of blanks removal is focused on obtaining
blades and microblades by manual pressing
method. Findings of round tablets are also associated
with the same cores, with the negatives of removing
flakes to correct the working platform.
In general, we can say that flint knapping occurred
mainly outside the site. This is evidenced by the ratio
of blades and flakes. There are almost three times
more blades than flakes. This circumstance suggests
that the site was visited sporadically, that the base
camp of visitors was situated in a different place.
The complex has 257 tools. The most numerous are
retouching blades, bladelets, and microblades and their
segments. Mostly, such products have a small semiflat
retouch along the edges, but there are also products
with alternative retouching. There are blades with
notches. Marked products with single wide notches
and products with 2—3 edge notches.
Burins also are represented in a large series. Burins
show a great typological diversity. There are burins on
truncated facetted blades, including bilateral burins.
There are many angle burins on broken blades. Often,
such blades are double. There is a symmetrical dihedral
burin. All of the listed burins are made on blades.
All transverse and dihedral angle burins are made on
flakes. There is one combined tool: burin on truncated
facetted blade — the endscraper.
Scrapers are very few in comparison with burins.
All of them are made on flakes, they are the endscrapers.
There is a series of chisels on massive segments of
blades and on flakes. Probably, some retouched flakes
were used as scrapers and chisels.
Truncated facetted blades are found, including oblique
truncated facetted blades and oblique truncated
facetted blade with a negative of microburins spall. A
fairly representative complex associated with hunting
weapons. This is a series of bladelets and microblades
with abrupt retouch.
In general, the typology of the assemblage indicates
that the site was used as temporary hunting camp
where a minimal number of production activities were
carried out.